(untitled) (Journal of Laboratory Animal Science, 2021)
The purpose of this study was to evaluate the effect of dissociative anesthesia in the oral administration of radiolabelled gastro-retentive Metformin tablet in New Zealand White rabbits. The radiolabelled tablet formulation was administered to the rabbit by oral route. In this pilot experiment, it was observed that maximum activity was retained in the oral cavity as compared to gastric area. Hence, to address this problem modification with oral gavaging was done. Intragastric administration of radiolabelled Metformin drug formulation under effect of dissociative anesthesia resulted in 92.6% retention of radioactive tablet in the gastric region with minimal esophageal contamination. Therefore, it was possible to carry out further experiments in these animals with successful administration of tablet followed by sequential scintigraphy imaging at different time intervals. Significant retention was observed up to 6 hrs. Judicious use of dissociative anesthesia helps to attempt the practical problems for oral administration of a tablet in laboratory animals. The procedure can be useful for further pre-clinical testing of newer drug formulations in tablet form.